Novel COL4A2 variant in a large pedigree: Consequences and dilemmas. Issue 4 (25th May 2017) - McGovern, M.; Flanagan, O.; Lynch, B.; Lynch, S.A.; Allen, N.M.
Abstract : Pathogenic COL4A2 variants cause abnormalities in collagen production and can have serious implications for a range of organ systems, most notably the brain. Herein, we describe a large family of first‐degree relatives affected by a novel heterozygous variant in COL4A2 (c.3490G.A). A wide disease spectrum is described, from asymptomatic to symptomatic, including 2 children with porencephaly and co‐existing juvenile idiopathic polyarthritis. During a subsequent pregnancy, antenatal testing identified a positive fetus. In view of the literature, we review management and genetic counselling dilemmas.